Post-fall reporting in aged acute inpatient mental health units: an 18-month observational cohort study - Furness, T.; Mnatzaganian, G.; Garlick, R.; Ireland, S.; McKenna, B.; Hill, Keith (Cambridge University Press, 2017)
Despite the high risk of falling for people with severe mental illness, there is limited falls research in mental health settings. Therefore, the objective of this observational cohort study was to conduct a focused post-fall review of fall episodes within aged acute inpatient mental health units at one of Australia's largest publicly funded mental health organizations.